The Effect of Aerobic Activity on Blood Sugar In BKMF Volleyball FIKK UNM Athletes (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the effect of aerobic activity on the increase in blood sugar in BKMF Volleyball FIKK UNM athletes. The research method uses a statistical test with the application of SPSS 21. The research sample consisted of 20 athletes whose blood sugar levels were tested before and after doing aerobic activities. The results of the analysis showed that the average blood sugar level before aerobic activity (pre-test) was 93.1500, while after aerobic activity (post-test) decreased to 82.8500. Statistical tests showed a significance value (sig. 2-tailed) of 0.000 (p